DIGITAL LIBRARY MANAGEMENT INFORMATION SYSTEM AT MADRASAH IBTIDAIYAH ALFAJAR PRINGSEWU IN AN EFFORT TO INCREASE STUDENT LITERACY - Warisno, Andi (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2024)
Study This aim for designing System Information Management Digital Library at Madrasah Ibtidaiyah Alfajar Pringsewu as effort increase literacy student. Research methods used is approach qualitative with steps research that includes analysis need system, design system with using the Unified Modeling Language (UML) model, and evaluation design. Data is collected through studies literature, interviews with staff library, as well observation to the management process library moment This. Research result show that design system information management customized digital library with needs of Madrasah Ibtidaiyah Alfajar Pringsewu can increase efficiency in management information, facilitating accessibility source power, and enrich experience Study student. Study This conclude that implementation system information governance management designed digital library in a way special can become step strategic in support effort increase literacy students at Madrasah Ibtidaiyah. System Information Digital Library, Madrasah Ibtidaiyah Alfajar Pringsewu can increase effectiveness system information governance management digital library in support effort increase literacy students and strengthen role library as center dynamic and inclusive learning.